2018
DOI: 10.1017/s0016756818000341
|View full text |Cite
|
Sign up to set email alerts
|

The first occurrence of the earliest species of Acadoparadoxides outside West Gondwana (Cambrian; Holy Cross Mountains, Poland)

Abstract: Two hundred and eighty specimens of paradoxidids from two localities in the Holy Cross Mountains (Poland) have been reanalysed using morphometric techniques. Revision of the dataset provided evidence for the presence of two endemic taxa: Acadoparadoxides kozlowskii (Orłowski, 1959) and Acadoparadoxides samsonowiczi (Orłowski, 1959), both belonging to the earliest group of Acadoparadoxides, initially considered to be present only in Gondwanan successions. Thus, this is the first description of the members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 26 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…First of all, not taking tectonic deformation into account may be risky: although in classic morphometrics the amount of deformation present in the sample may be negligible, geometric morphometrics is more vulnerable to such distortion. In a recent study, Nowicki & Żylińska (2018) have tested the utility of geometric morphometric analyses on species of Acadoparadoxides from lowermost middle Cambrian strata of the Holy Cross Mountains, Poland. Nowicki & Żylińska (2018) noted a study by Angielczyk & Sheets (2007), which concluded a comprehensive validation of numerical retrodeformation techniques in geometric morphometrics.…”
Section: B Morphometricsmentioning
confidence: 99%
See 3 more Smart Citations
“…First of all, not taking tectonic deformation into account may be risky: although in classic morphometrics the amount of deformation present in the sample may be negligible, geometric morphometrics is more vulnerable to such distortion. In a recent study, Nowicki & Żylińska (2018) have tested the utility of geometric morphometric analyses on species of Acadoparadoxides from lowermost middle Cambrian strata of the Holy Cross Mountains, Poland. Nowicki & Żylińska (2018) noted a study by Angielczyk & Sheets (2007), which concluded a comprehensive validation of numerical retrodeformation techniques in geometric morphometrics.…”
Section: B Morphometricsmentioning
confidence: 99%
“…According to the results of Nowicki & Żylińska (2018), the removal of a principal component that is best correlated with the length:width proportions does not improve the outcome when the axial symmetry is not restored in the specimens before the procedure. A procedure known as symmetrization improves the results, but can be safely applied only to specimens in which the deformation is relatively simple, without a high amount of noise added to the deformation, which would compromise the apparent significance of those analyses.…”
Section: B Morphometricsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the Polish specimens seem to have an older occurrence in the Holy Cross Mountains than those from the type area in southern Sweden (Żylińska and Szczepanik 2009). These specimens have been recently reassigned to the endemic species Acadoparadoxides kozlowskii (Orłowski, 1959a) and bear no resemblance to Eccaparadoxides (Nowicki and Żylińska 2019). Westergård, 1936), known from Öland and Jämtland in Sweden, from the Oslo district in southern Norway, and from the Peribaltic Depression in northern Poland, is usually regarded as a species of Acadoparadoxides.…”
Section: Taxa From Balticamentioning
confidence: 99%